Impact of water relations on the production, ecological fitness and stability of the biocontrol fungus Metarhizium anisopliae - Ypsilos, Ioannis K. (Cranfield University, 2004)
The aim of this work was the production of high numbers of propagules of the entomopathogenic fungus Metarhizium anisopliae with high germination capacity under low water availability, good storage stability and enhanced pathogenicity. To this end modifications of cultural conditions were employed. Water-stress in solid substrate fermentation reduced the conidial production but resulted in enhancement of germination capacity. Conidial production and germination was also considerably influenced by the type of solid substrate (bulgar wheat, millet grain). Intracellular accumulation of endogenous reserves of selected polyols, which have been linked with enhancement of germination under conditions of restricted water availability, was altered by such substrate modifications. Imposed water-stress in liquid culture resulted in increased blastospore production in the 0.998 to 0.96 water activity (a. ) range when ionic solutes (NaCl, KCI) were used for medium modification but when PEG 200 was used, this range was narrower (0.998-0.98 aw). Water-stress resulted in the production of modified blastospores with increased levels of the low molecular weight polyol erythritol. Higher amounts of endogenous polyols were retained intracellularly when modified blastospores were harvested in isotonic solutions compared to those subjected to hypo-osmotic shock by washing with water. Intracellular polyol patterns of blastospores were also affected by nitrogen source, pH and aW-modifying solute as well as by interaction between these factors. Optimum conditions for increased erythritol accumulation occurred when ionic solutes (NaCl, KCl) were used for aW modification and in the pH range between 6.8-8. Total endogenous protein was also enhanced under the same conditions. Germination of blastospores produced under these conditions was between 62-89% under conditions of water-stress (0.96 a, ). In contrast, blastospores with lower amounts of erythritol and total protein content had decreased germination (8- 67%). Osmoprotection of such modified blastospores resulted in increased storage stability as wet pastes and as freeze-dried preparations. Fluidised bed dried blastospores had either decreased viability (<25%) or good viability (>40%) but high conent of moisture (>30%). Destruxin A production was not affected by osmoprotection whereas protease activity was enhanced by isotonic washing with PEG 200 solution but not by. ionic (NaCl) or carbohydrate (glucose) solutions. Modified blastospores were not more infective to aphids than unmodified ones under 100% R. H. regimes.